The new frontier - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The new frontier: farmer responses to land degradation - a West African study by Kojo Sebastian Amanor 1994 244pp ISBN 1 85649 242 7 Zed Books Ltd, 7 Cynthia Street, London N1 9JF, UK available from CTA